Brave new world : imperial and democratic nation-building in Britain between the wars - Beers, Laura, 1978-; Thomas, Geraint (Historian) (Humanities Digital Library., 2011)
Brave New World reappraises the domestic and imperial history of Britain in the inter-war period, investigating how 'nation building' was given renewed impetus by the upheavals of the First World War. The essays in this collection address how new technologies and approaches to governance were used to forge new national identities both at home and in the empire, covering a wide range of issues from the representation of empire on film to the convergence of politics and 'star culture'.--